The relationship between smoking status and depression prevalence among first and second year medical students - Marakoğlu, Kamile; Çivi, Selma; Şahsıvar, Şule; Özdemir, Saniye (Journal of Dependence, 2006)
Objective: The aim of this study was to investigate relationship between smoking attitudes and depression prevalence among first and second year students of Meram Medical Faculty, Selçuk University.Method: In this descriptive and cross-sectional study we administered a questionnaire and Beck Depression Inventory (BDI) that has 21 questions to students in order to determine socio-demographic, smoking and depression status at first and second year in medical school. The study was carried out between February and March in 2006. X2 test was used for statistical analysis.Results: We reached 81.9% of total students (331/404) during the study period. The mean age was 19.51±1.37. As looked at the distribution of gender, 56.2% of them were male (186) and 43.8% of them were female (145). Smoking prevalence was detected as 16.0% (53/331). BDI score was found over 10 in 43.8% (145/331). According to BDI scores, depression degree was mild in 24.8% (82/331), moderate in 12.1% (40/331) and severe in 6.9% (23/331) of students. The mean BDI score was 11.13±7.9 (median=9, min=0, max=38) in female students and 8.96±8.27 (median=7, min=0, max=48) in male students. Depression scores of smokers were higher than non-smokers (p>0.05). Depression scores and smoking prevalence of students who live with their families were lower than the ones who live at hostel or other places (p>0.05). The smoking prevalence of smoker students families was found as high significant (p
Keywords: Depression; smoking; student